2016
DOI: 10.1111/cei.12750
|View full text |Cite
|
Sign up to set email alerts
|

Lupus anti-ribosomal P autoantibody proteomes express convergent biclonal signatures

Abstract: SummaryLupus-specific anti-ribosomal P (anti-Rib-P) autoantibodies have been implicated in the pathogenesis of neurological complications in systemic lupus erythematosus (SLE). The aim of the present study was to determine variable (V)-region signatures of secreted autoantibody proteomes specific for the Rib-P heterocomplex and investigate the molecular basis of the reported cross-reactivity with Sm autoantigen. Anti-Rib-P immunoglobulins (IgGs) were purified from six anti-Rib-P-positive sera by elution from e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Total lane reactivity was quantified by drawing a transect through each lane, subtracting background and integrating the total reactivity in each lane as previously described [32]. 2D electrophoresis of 100 lg of raw or 2-h boiled peanut extracts using pI 3-11 nonlinear IPG strips (Bio-Rad) and 4-20% Criterion Stain Free polyacrylamide gels (Bio-Rad) was performed as previously described [33].…”
Section: Sds-page Western Blot and Two-dimensional Electrophoresismentioning
confidence: 99%
“…Total lane reactivity was quantified by drawing a transect through each lane, subtracting background and integrating the total reactivity in each lane as previously described [32]. 2D electrophoresis of 100 lg of raw or 2-h boiled peanut extracts using pI 3-11 nonlinear IPG strips (Bio-Rad) and 4-20% Criterion Stain Free polyacrylamide gels (Bio-Rad) was performed as previously described [33].…”
Section: Sds-page Western Blot and Two-dimensional Electrophoresismentioning
confidence: 99%
“…In this study, we performed the first proteomic profiling of secreted (serum) RF responses in primary SS using a simple purification method for RF heavy chains followed by de novo Ig sequencing and database matching. As reported for other systemic autoantibodies in lupus and primary SS, such as anti‐Ro/La, anti‐Sm, and anti–ribosomal P, serum IgM‐RF repertoires express shared sets of Ig V H subfamilies and reveal moderate levels of somatic hypermutation . While an early study of RF hybridomas reported a diverse usage of germline‐encoded Ig V H genes in primary SS, single‐cell studies provide a limited view of the actual secreted RF repertoire in comparison with direct high‐resolution mass spectrometric sequencing .…”
Section: Discussionmentioning
confidence: 99%
“…In-gel tryptic and chymotryptic digests were performed on the 50 kD H-and 25 kD L-chain bands and peptides analysed using a TripleTOF 5600+ mass spectrometer (AB Sciex, Framingham, MA, USA) coupled to an Ekspert nano LC 415 high-performance liquid chromatography (HPLC) (Eksigent; AB Sciex), as detailed previously [17,18,[21][22][23][24]. Parameters for database searches, data refinement and IgV gene family assignments have been described previously [17,18,[21][22][23][24]31]; in brief, a maximum of two missed cleavages, precursor tolerance of < 15 parts per million, product ion tolerance of 0·02 Da, precursor charge state of +2 to +4, fixed modification carbamidomethylation, variable modifications oxidation and deamidation, a maximum of three modifications allowed and non-specific cleavage at one end. 1).…”
Section: Mass Spectrometry (Ms) Sequencing and Protein Sequence Data mentioning
confidence: 99%
“…We have developed proteomic methodology within our facility to analyse immunoglobulin (Ig)V peptide repertoires of anti-Ro/La autoantibodies in primary Sjögren's syndrome (SS) and anti-Sm and anti-ribosomal P responses in SLE, based on high-resolution mass spectrometric sequencing of specific autoantibodies purified from stored serum samples [17][18][19][20][21][22][23]. In brief, anti-Ro/La proteomes comprised oligoclonal expression patterns of shared, heavily mutated heavy (H)-and light (L)-chains with anti-Ro60 IgV molecular peptide fingerprints of anti-Ro/La determinant spreading [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation